Kejadian Penyakit Kulit Akibat Kebiasaan Anak-Anak Mandi di Suangai Tello Kota Makassar - Putri, Safridha Kemala; Pannyiwi, Rahmat; Juwariyah, Siti; Syarief, Syarifah Wahyuni Al; Wiranti, Bhakti; Nurseskasatmata, Satria Eureka (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
Clean and healthy living behavior is the main factor determining people's health status. Skin disease is a common disease that occurs at all ages. Skin diseases can be caused by several factors, namely living habits and the environment. Skin diseases can develop in poor personal hygiene and environmental hygiene conditions. Bathing habits are one of the factors associated with the incidence of dermatitis. Bathing is an important part of maintaining personal hygiene. Bathing can eliminate odors, remove dirt, stimulate blood circulation, and provide freshness to the body. It's best to shower twice a day, the main reason is to keep your body healthy and fresh. Many factors cause skin diseases, one of which is bathing habits. Water is the main requirement for life processes on earth, so there would be no life if there was no water on earth. However, water can be disastrous if it is provided in incorrect conditions, both in quality and quantity. Humans really need clean water, both for daily needs such as drinking, bathing, washing and so on. The target village is being revitalized with the aim of increasing public knowledge about the causes of dermatitis. Based on the results of interviews with village communities, the problem is the low level of public knowledge about the causes of dermatitis. To overcome the problems faced, namely outreach to increase public knowledge about the causes of dermatitis in the village.